The politics of Shari'a law: Islamist activitists and the state in democratizing Indonesia - Buehler, Michael (Cambridge, UK Cambridge University Press, 2016)
"The Islamization of politics in Indonesia after 1998 presents an underexplored puzzle: why has there been a rise in the number of shari'a laws despite the electoral decline of Islamist parties? Michael Buehler presents an analysis of the conditions under which Islamist activists situated outside formal party politics may capture and exert influence in Muslim-majority countries facing democratization. His analysis shows that introducing competitive elections creates new pressures for entrenched elites to mobilize and structure the electorate, thereby opening up new opportunities for Islamist activists to influence politics. Buehler's analysis of changing state-religion relations in formerly authoritarian Islamic countries illuminates broader theoretical debates on Islamization in the context of democratization. This timely text is essential reading for students, scholars, and government analysts"--
"The Islamization of politics in Indonesia after 1998 presents an underexplored puzzle: Why has there been a rise in the number of shari'a laws despite the electoral decline of Islamist parties? Michael Buehler presents an analysis of the conditions under which Islamist activists situated outside formal party politics may capture and exert influence in Muslim-majority countries facing democratization. He argues that introducing competitive elections creates new pressures for entrenched elites to mobilize and structure the electorate, thereby opening up new opportunities for Islamist activists to influence politics. Buehler's analysis of changing state-religion relations in formerly authoritarian Islamic countries illuminates broader theoretical debates on Islamization in the context of democratization. This timely text is essential reading for students, scholars, and government analysts"--
Machine generated contents note: List of abbreviations; Acknowledgements; Introduction; 1. How state elites mediate the influence of Islamist activists in Indonesia; 2. Islamist activism, the state and shari'a policymaking between 1945 and 1998; 3. State elites and institutional change; 4. The accumulation and exercise of power in local politics after 1998; 5. Islamist parties after 1998: mobilization without influence; 6. The mobilization and lobbying efforts of Islamist movements after 1998; 7. Providing political resources in exchange for the adoption of shari'a regulations; 8. Conclusion: summary of findings and avenues for future research; Appendix 1; Appendix 2; Appendix 3; Bibliography; Index.
Includes bibliographical references
Keywords: Law; Indonesia- Government and Politics; Islam and politics